MEMBANGUN KEUNGGULAN BERSAING DENGAN METODE ANALISIS SWOT 8 KUADRAN PADA PERBANKAN SYARIAH ( STUDI PADA BRI SYARIAH KOTA BATAM ) - Erman Syah (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2018)
The development of Islamic banking in mature growing very rapidly, Islamic banking is considered as an alternative option for people who want to trade in sharia, Islamic banks are present in the community began in 1992, andthe institution until 2017 there were 12 Islamic banks, 22 Sharia Islamic rural banks and 155 units BPR in Indonesia, a very tight competition in the banking industry led to a strategy that should be done by the banking system. BRI Syariah Batam as a new Islamic bank in the Islamic banking industry and nationally are expected to compete for the national market share.The purpose of this study whether strategy should BRI Syariah Batam in order to be able to compete Kepualauan Riau, To know the strategies that should be used by the author using SWOT 8 Quadrant.From the results of research by analyzing the internal and external corporate Batam found that BRI Syariah expected to apply aggressive growth strategy by way of market penetration, market development and product development.